A Study of Public Sphere: Coffeehouses from the Ottoman Empire to the Early Republican Period - Nevzat Erdogan; Mehmet Özalper (Anemon Muş Alparslan Üniversitesi Sosyal Bilimler Dergisi, 2026)
Coffeehouses emerged as a result of the widespread consumption of coffee, an aromatic plant, as a beverage. Coffee, whose homeland is Abyssinia, was first transported to Yemen and later to Mecca by merchants in the fifteenth century, and it became part of social life in the Ottoman Empire in the mid-sixteenth century. Coffeehouses, where coffee drinkers gathered, became places in which all kinds of ideas, whether true or not, were discussed and disseminated. In the Ottoman Empire, coffeehouses faced closure for a period on the grounds that they were places where political ideas against the state attracted supporters. However, beginning with the Tanzimat and continuing through the Constitutional Period, they became important places where every movement of change and transformation was experienced, discussed, and criticized. As the function and importance of coffeehouses in social life increased, they also came to serve as instruments of political communication. During the years of the War of Independence, coffeehouses became places where the public was informed about the activities carried out by the First Assembly, national societies, and the Kuva-yı Milliye, where all kinds of news circulated, and where national consciousness spread. This study examines the social and political functions of coffeehouses and the changes they underwent during the historical period extending from the Ottoman Empire to the Early Republican period. In addition, it investigates the positive and negative roles of coffeehouses, which became widespread public spaces, in political communication.